RADIKALISME ISLAM POPULER: ANALISIS WACANA KRITIS TERHADAP BAHASA USTAZ SELEBRITIS DALAM AKSI BELA ISLAM - Makyun Subuki (Widyaparwa, 2023)
The sequences of actions to defend Islam at the end of 2016 were often called the rise of Indonesia's radical Islam. This paper attempts to describe the Indonesian radical Islamic movement in motivating the masses to engage in acts of defending Islam. The data in this paper comes from the discursive practices of islamic televangelists quoted in the mass media. The data was collected through document study and categorized based on the Fairclough model of critical discourse analysis framework. Based on the analysis conducted, there are three important findings. First, textually, the discursive practices of islamic televangelists mobilizing people in actions to defend Islam have an intertextual relationship with the discursive practices of radical Islamic figures in Indonesia. Second, their discursive practices eventually form an order of discourse regarding Islamic movements from the point of view of radical popular Islam. Third, based on an analysis of the dimensions of social practice, the order of discourse regarding Islamic movements will further motivate Muslims to engage in actions to defend Islam.Rangkaian aksi bela Islam di akhir 2016 disebut sebagai bangkitnya Islam radikal Indonesia. Tulisan ini mencoba untuk memerikan gerakan Islam radikal Indonesia dalam memotivasi massa untuk terlibat dalam aksi bela Islam. Data dalam tulisan ini berasal dari praktik diskursif ustaz selebritis yang dikutip di media massa. Data dikumpulkan melalui studi dokumen dan dikategorisasi berdasarkan kerangka kerja analisis wacana kritis model Fairclough. Berdasarkan analisis yang dilakukan, terdapat tiga temuan penting. Pertama, secara tekstual, praktik diskursif ustaz selebritis menggerakkan umat dalam aksi bela Islam memiliki hubungan intertekstual dengan praktik diskursif tokoh Islam radikal di Indonesia. Kedua, praktik kewacanaan mereka akhirnya membentuk sebuah order of discourse mengenai gerakan Islam dari sudut pandang Islam populer yang radikal. Ketiga, berdasarkan analisis dimensi praktik sosial, order of discourse tentang gerakan Islam selanjutnya turut memberikan motivasi kepada umat Islam terlibat dalam aksi bela Islam.